2007
DOI: 10.1080/10790268.2007.11753911
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal Stimulation Causes Increased Colonic Motor Activity in Subjects With Spinal Cord Injury

Abstract: Background: Difficulty with evacuation (DWE) is a major problem after spinal cord injury (SCI). Stimulation of the anal canal and lower rectum, accomplished using a gloved finger (so-called digital rectal stimulation or DRS) is often used as an adjunct to laxatives and enemas to facilitate bowel evacuation. However, the basis for the efficacy of DRS is not known. This study assessed the effect of DRS on colonic motility.Methods: Six subjects with SCI were studied several hours after a bowel care session. Colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 14 publications
0
30
0
5
Order By: Relevance
“…There is Level 4 evidence (from one pre-post study; N ¼ 6) ( Table 4) that digital rectal stimulation increases motility in the left colon by activating preserved anorectal colonic reflexes. 25 Abdominal massage. There is Level 4 evidence (from one pre-post study; N ¼ 24) that abdominal massage significantly shortened total colonic transit time, reduced abdominal distension, and increased frequency of bowel movements per week (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is Level 4 evidence (from one pre-post study; N ¼ 6) ( Table 4) that digital rectal stimulation increases motility in the left colon by activating preserved anorectal colonic reflexes. 25 Abdominal massage. There is Level 4 evidence (from one pre-post study; N ¼ 24) that abdominal massage significantly shortened total colonic transit time, reduced abdominal distension, and increased frequency of bowel movements per week (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…One study 25 showed that digital rectal stimulation increases peristaltic waves in the left colon, thus increasing motility in this segment. Gastrocolonic and anorectal reflexes can be successfully incorporated into a bowel routine for individuals with SCI.…”
mentioning
confidence: 99%
“…A adoção de hábitos saudáveis com relação à dieta devem ser indicados (2,9,11,(16)(17)(18) . Pode-se orientar a construção de refeições balanceadas, com cardápio rico em fibras.…”
Section: Risco De Constipaçãounclassified
“…Os sinais da impactação fecal são a ausência de eliminação de fezes por vários dias ou quando há eliminação de apenas exudatos fluidos de fezes (14) . As intervenções indicadas para o Risco de constipação também se aplicam ao diagnóstico de Constipação, sendo pertinente apontar outras intervenções de enfermagem, como por exemplo, a administração de medicamentos (2,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Em alguns casos, sob prescrição médica, cabe ao enfermeiro a administração de laxantes orais ou supositórios, sendo esses indicados após tentativas terapêuticas não farmacológicas sem Vasconcelos (2,11,16,18) .…”
Section: Constipaçãounclassified
See 1 more Smart Citation